Introduction to special issue: Gender and rural development: Sustainable livelihoods in a neoliberal context - Basu, P.; Galiè, Alessandra (MDPI, 2021)
This editorial introduces the articles that are part of the Special Issue on ‘Gender and Rural Development: Sustainable Livelihoods in a Neoliberal Context.’